PEMANFAATAN MEDIA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SEBAGAI UPAYA MENINGKATKAN MINAT PESERTA DIDIK DI SMP ALAM INSAN MULIA KOTA LUBUKLINGGAU - Mukhdori Ali Maksum (UNISAN JURNAL, 2025)
This study aims to explore the importance of learning media in increasing students’ interest and motivation to learn. This study uses a literature study method that relies on bibliographic sources from articles in the latest journals and books related to the main content of the problem and reading data with the thoughts of experts with a constructive approach and interpretation of the main content of the discussion. The results of the study indicate that varied, creative, and innovative learning media, such as videos, interactive applications, and other tools, can significantly increase students’ interest and motivation to learn. Teachers at SMP Alam Insan Mulia Kota Lubuklinggau implement technology-based learning strategies and methods such as Problem-Based Learning (PBL) and Cooperative Learning to create an interesting and relevant learning atmosphere. However, limited facilities, technological constraints, and lack of skills of senior teachers in using technology are the main challenges. The solutions implemented include an individual approach, innovation of learning media, and empowerment of students in making media. Based on the results of the questionnaire, 82% of students support the use of learning media, indicating the effectiveness of visual and interactive media in increasing student understanding and participation. This study emphasizes the importance of the role of teachers in utilizing learning media to create more meaningful, effective, and efficient learning, so as to improve the quality of education in elementary schools, especially in areas with limited facilities.